2015
DOI: 10.4314/ahs.v15i3.24
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of lactic acid bacteria isolated from cow faeces against potential enteric pathogens

Abstract: Background: The addition of sub therapeutic doses of antibiotics to cattle feed for growth promotion is a contributory factor to antibiotic resistance, thus an alternative to antibiotics is needed in animal feed additives. Objective: To determine the antimicrobial activity of cow's intestinal Lactic acid bacteria (LAB) against enteric commensals. Method: Escherichia coli, Klebsiella species (spp) and LAB were isolated from thirty different cow faecal samples and the LAB identified by partial sequencing of 16S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 15 publications
1
25
2
Order By: Relevance
“…According to [ 6 , 47 , 66 , [68] , [69] , [70] ] the antibacterial activities displayed by the antagonizing bacteria are as a result of production of antibacterial agents Surfactin and bacteriocin which include mersacidin and erisin are some of the antibacterial compounds produced by Bacillus species responsible for their antibacterial activities [ 23 , [71] , [72] , [73] , [74] ]. Brochocin-C is a bacteriocin produced by Brochothrix species, known for its broad spectrum activity [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to [ 6 , 47 , 66 , [68] , [69] , [70] ] the antibacterial activities displayed by the antagonizing bacteria are as a result of production of antibacterial agents Surfactin and bacteriocin which include mersacidin and erisin are some of the antibacterial compounds produced by Bacillus species responsible for their antibacterial activities [ 23 , [71] , [72] , [73] , [74] ]. Brochocin-C is a bacteriocin produced by Brochothrix species, known for its broad spectrum activity [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only E. mundtii J5 produced antilisterial activity after the pH was adjusted. Other studies evaluating the bacteriocin-like substances from enterococci showed similar data to this (Birri et al, 2010;Adeniyi et al, 2015). Birri et al (2010) worked with the supernatant of 104 LAB study from the gastrointestinal tracts of children, and only one isolate of E. avium (0.96%) was a producer of an antagonist substance.…”
Section: Discussionmentioning
confidence: 54%
“…The antimicrobial activities of beneficial microorganisms particularly lactic acid bacteria isolated from various sources against pathogens have been reported by many authors [7,36].…”
Section: Antimicrobial Potentials Of Beneficial Microbes Against Antimentioning
confidence: 98%
“…This co-administration is done with the hope that this action will reduce antibiotic selective pressure, and decrease the emergence of drug-resistant pathogens. Currently, research is ongoing on the packaging of lyophilized lactic acid bacteria into capsules so that they can be used in the veterinary field (as probiotics) to inhibit the proliferation of zoonotic pathogens [36]. This method will limit the spread of diseases from animals to humans through animal-derived products.…”
Section: Current Applicationsmentioning
confidence: 99%